Crossdressing Cinema: An Analysis of Transgender Representation in Film - Miller, Jeremy Russell (2012)
Transgender representations generally distance the transgender characters from the audience as objects of ridicule, fear, and sympathy. This distancing is accomplished through the use of specific narrative conventions and visual codes. In this dissertation, I analyze representations of transgender individuals in popular film comedies, thrillers, and independent dramas. Through a textual analysis of 24 films, I argue that the narrative conventions and visual codes of the films work to prevent identification or connection between the transgender characters and the audience. The purpose of this distancing is to privilege the heteronormative identities of the characters over their transgender identities. This dissertation is grounded in a cultural studies approach to representation as constitutive and constraining and a positional approach to gender that views gender identity as a position taken in a specific social context. Contributions are made to the fields of communication, film studies, and gender studies through the methodological approach to textual analysis of categories of films over individual case studies and the idea that individuals can be positioned in identities they do not actively claim for themselves. This dissertation also makes a significant contribution to conceptions of the gaze through the development of three transgender gazes that focus on the ways the characters are visually constructed rather than the viewpoints taken by audience members. In the end, transgender representations work to support heteronormativity by constructing the transgender characters in specific ways to prevent audience members from developing deeper connections with them.
Accepted: 2012-10-19T15:30:33Z
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé